A New Method of Power Arithmetic for Parallel Inverter - Wang, Hongliang; Xie, Yinyin; Pei, Xuejun; Kang, Yong; Yue, Xiumei (Elektronika ir Elektrotechnika, 2010)
To overcome the one fundamental cycle delay of the conventional power arithmetic under the load change, a new method of power arithmetic is proposed, which rebuilds the sinusoidal signal only using the last-value and next value of signal in discrete domain. Thus, it is able to fast calculate power value and can obtain the true power value only in one sampling cycle. Moreover, it occupies much smaller DSP space and cuts down computing process, as the sine and cosine tables are cancelled. The high precision of proposed method has validated through comparison with the ideal and simulation values of active, reactive power. Experimental results from a two-75-kVA- inverters system show the proposed method is practicable.